Dynamical response of a prestrained system comprising a substrate and bond and covering layers to a moving load - Dincsoy, E.; Guler, C.; Akbarov, S. D. (SPRINGER, 2009)
The dynamical response of a system consisting of a prestressed substrate and covering and bond layers to a moving load is investigated within the scope of a piecewise-homogeneous body model by using a three-dimensional linearized theory of wave propagation in initially stressed bodies. It is assumed that the materials of the constituents are isotropic and homogeneous, and the subsonic speed of the moving load acting on the covering layer is constant. The investigations are carried out for a plane strain state under complete and in complete contact conditions. For various values of problem parameters, numerical results for the critical speed are presented and discussed.
Keywords: moving load; critical speed; initial stress; dynamical response; bond layer; covering layer; substrate; INTERFACE STRESS-FIELD; Mechanics; Materials Science; Polymer Science